2001
DOI: 10.1021/cc010045b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Resins via Multiparallel Suspension Polymerization

Abstract: A system for the multiparallel synthesis of polymer resins for solid-phase synthesis is presented, accelerating the preparation of new resins using standard suspension polymerization protocols. The system was evaluated by preparing a range of polystyrene resins with well-defined characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 5 publications
0
11
0
1
Order By: Relevance
“…After the previously reported automated parallel suspension polymerization of styrene, divinylbenzene, and vinylbenzylchloride by Bradley and co-workers, [34] the first example of automated parallel emulsion polymerization has been reported by Schubert, Van Herk and co-workers. [35] Emulsion polymerizations were performed in five parallel reactors utilizing well-defined systems of styrene and vinyl acetate, whereby the vortex speed was identified as an important parameter to obtain suitable emulsions.…”
Section: Free Radical Polymerizationmentioning
confidence: 99%
“…After the previously reported automated parallel suspension polymerization of styrene, divinylbenzene, and vinylbenzylchloride by Bradley and co-workers, [34] the first example of automated parallel emulsion polymerization has been reported by Schubert, Van Herk and co-workers. [35] Emulsion polymerizations were performed in five parallel reactors utilizing well-defined systems of styrene and vinyl acetate, whereby the vortex speed was identified as an important parameter to obtain suitable emulsions.…”
Section: Free Radical Polymerizationmentioning
confidence: 99%
“…[45][46][47] This system was used to perform the parallel synthesis of a set of polystyrene resins. Polymerizations with varying ratios of divinylbenzene (DVB), styrene and vinylbenzyl chloride were thermally initiated with 2,2 0 -azoisobutyronitrile (AIBN).…”
Section: Free-radical Polymerizationmentioning
confidence: 99%
“…No more than one semiautomated (manual-filling) example on suspension polymerization has been reported utilizing six large-scale (500-mL) parallel reactors equipped with mechanical stirrers. 27 However, emulsion polymerizations are especially interesting for the ease of product isolation and handling. Stirred tank reactors are used for emulsion polymerizations, particularly for semibatch operations.…”
Section: Emulsion Polymerizationmentioning
confidence: 99%
“…Moreover, both free-and controlled radical polymerizations have been described in the literature. Alesso et al 27 synthesized several polystyrene beads via automated suspension free-radical polymerization of styrene and divinylbenzene, and Voorn et al 28 demonstrated the successful application of automated parallel methods to the emulsion polymerization of styrene and vinyl acetate. Other combinatorial and automated free-radical polymerizations in solution were reported by Gravert et al, 29 Lanza et al, 30,31 Williamson and Long, 32 as well as Symyx.…”
Section: Introductionmentioning
confidence: 99%